Acupuncture and related therapies for carpal tunnel syndrome: A protocol for systematic review and Bayesian network meta-analysis. Issue 50 (17th December 2021) - Bian, Zhiyuan; Yu, Jie; Tu, Mingqi; Liao, Binjun; Huang, Jingmei; Jiang, Yongliang; Fang, Jianqiao
Abstract: Background: Carpal tunnel syndrome (CTS) is the most common peripheral nerve compression syndrome of the upper limb. Plenty of studies showed the effects of acupuncture therapy on relieving pain and improving functional status for CTS patients. Diverse types of acupuncture therapies have been used in the treatment for CTS, but their relative treatment effects are poorly understood. This study will evaluate the effects of different acupuncture and related therapies for CTS by conducting a systematic review and Bayesian network meta-analysis (NMA). Methods: We will search randomized controlled trials (RCTs) of acupuncture and related therapies for CTS in MEDLINE (via PubMed), EMBASE, Web of Science, Cochrane Library, Chinese Biomedical Database, China National Knowledge Infrastructure, VIP Database, Wanfang Database, WHO International Clinical Trials Registry Platform, ClinicalTrials.gov, Chinese Clinical Trial Register, and OpenGrey from inception to November 2021. Then, we will select eligible studies, extract data, and conduct risk of bias assessment using the Cochrane tool. Pairwise meta-analysis and Bayesian NMA will be performed in Stata 15.1 software and Aggregate Data Drug Information System 1.16.8 software. We will assess the quality of the evidence using the Confidence in Network Meta-Analysis application. Results: In this study, the treatment effects and safety of different acupuncture and related therapies for CTS will be evaluated. Conclusion: This study will provide evidence for choosing the optimal acupuncture and related therapies in the treatment for CTS.